Generalized Method to Extract Carrier Diffusion Length from Photoconductivity Transients: Cases of BiVO_{4}, Halide Perovskites, and Amorphous and Crystalline Silicon - Markus Schleuning; Moritz Kölbach; Fatwa F. Abdi; Klaus Schwarzburg; Martin Stolterfoht; Rainer Eichberger; Roel van de Krol; Dennis Friedrich; Hannes Hempel (PRX Energy, 2022)
Long diffusion lengths of photoexcited charge carriers are crucial for high power conversion efficiencies of photoelectrochemical and photovoltaic devices. Time-resolved photoconductance measurements are often used to determine diffusion lengths in conventional semiconductors. However, effects such as polaron formation or multiple trapping can lead to time-varying mobilities and lifetimes that are not accounted for in the conventional calculation of the diffusion length. Here, a generalized analysis is presented that is valid for time-dependent mobilities and time-dependent lifetimes. The diffusion length is determined directly from the integral of a photoconductivity transient and can be applied regardless of the nature of carrier relaxation. To demonstrate our approach, photoconductivity transients are measured from 100 fs to 1 µs by the combination of time-resolved terahertz and microwave spectroscopy for BiVO_{4}, one of the most studied metal oxide photoanodes for photoelectrochemical water splitting. The temporal evolution of charge carrier displacement is monitored and converges after about 100 ns to a diffusion length of about 15 nm, which rationalizes the photocurrent loss in the corresponding photoelectrochemical device. The presented method is further validated on a-Si:H, c-Si, and halide perovskite, which underlines its potential to determine the diffusion length in a wide range of semiconductors, including disordered materials.